The effectiveness of water treatment processes against schistosome cercariae: A systematic review. - Laura Braun; Jack E T Grimes; Michael R Templeton (Public Library of Science (PLoS), 2018)
Schistosomiasis is one of the most disabling neglected tropical diseases, ranking second in terms of years lived with disability. While treatment with the drug praziquantel can have immediate beneficial effects, reinfection can occur rapidly if people are in contact with cercaria-infested water. Water treatment for schistosomiasis control seeks to eliminate viable cercariae from water, thereby providing safe alternative water supplies for recreational and domestic activities including laundry and bathing. This provision may reduce contact with infested water, which is crucial for reducing reinfection following chemotherapy and cutting schistosome transmission.A qualitative systematic review was carried out to summarize the existing knowledge on the effectiveness of water treatment in removing or inactivating human schistosome cercariae. Four online databases were searched. Studies were screened and categorized into five water treatment processes: storage, heating, chlorination, filtration, and ultraviolet (UV) disinfection.All five water treatment methods can remove or inactivate cercariae in water, and hence produce cercaria-free water. However, reliable design guidelines for treating water do not exist as there are insufficient data. Overall, the review found that cercariae are inactivated when storing water for 10-72 hours (depending on temperature), or with chlorination values of 3-30 mg-min/l. UV fluences between 3-60 mJ/cm2 may significantly damage or kill cercariae, and sand filters with 0.18-0.35 mm grain size have been shown to remove cercariae. This systematic review identified 67 studies about water treatment and schistosomiasis published in the past 106 years. It highlights the many factors that influence the results of water treatment experiments, which include different water quality conditions and methods for measuring key parameters. Variation in these factors limit comparability, and therefore currently available information is insufficient for providing complete water treatment design recommendations.